The Impact of Automation on the Future of Accountancy Profession - Ela Widasari; Hanifah Hanifah; Susana Dewi; Firmansyah Firmansyah (Yayasan Adra Karima Hubbi, 2024)
Background. Automation is transforming the accountancy profession, reshaping traditional roles and introducing new dynamics within the field. With advancements in artificial intelligence and machine learning, routine accounting tasks such as data entry, transaction processing, and report generation are increasingly automated, reducing the need for manual intervention. Purpose. This shift raises questions about the future role of accountants and the skills necessary to adapt to a more technology-driven environment. This study investigates the impact of automation on the accountancy profession, examining both the opportunities for increased efficiency and the potential challenges for professionals Method. A mixed-methods research approach was utilized, combining quantitative analysis of automation trends in accounting practices with qualitative insights from industry professionals. Data on the adoption of automated tools in accounting were analyzed to assess changes in productivity, error rates, and task completion times, while interviews with accountants provided perspectives on the evolving skillsets and competencies required. Results. Findings reveal that automation enhances efficiency by reducing errors and increasing productivity; however, it also necessitates a shift toward analytical and advisory roles, requiring accountants to develop new competencies in data interpretation and strategic decision-making Conclusion. The study concludes that automation will redefine the accountancy profession, with technology taking over repetitive tasks and creating opportunities for value-added roles. Accountants will need to focus on skills such as critical thinking, data analysis, and advisory functions to remain competitive. This shift underscores the importance of continuous learning and adaptability as essential components for future success in the field of accountancy.